Letter and obituaries of Moritz Wagner - Wagner, Moritz, 1813-1887.
ALS (1879 February 7) from Wagner to an unknown recipient and three obituaries for him from German newspapers.
German naturalist. Full name: Moritz Friedrich Wagner.
Collection material in German.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Naturalists